2015
DOI: 10.1177/0146167215580777
|View full text |Cite
|
Sign up to set email alerts
|

Adding Insult to Injury

Abstract: Intimates regularly confront their partners to motivate them to change undesirable behaviors. Nevertheless, contextual perspectives suggest that qualities of the partner may determine the implications of such attempts. Consistent with these ideas, a pilot study of romantic relationships, an observational study of newlyweds, and a diary study of married couples demonstrated that partner depression moderates the association between confrontational partner-regulation behaviors and partners' motivation, such that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Results showed that direct regulation attempts, regardless of opposing versus cooperative, were significantly associated with increased partner behavior change (standardized partial regression coefficients of direct-opposing attempts were .23, and standardized partial regression coefficients of direct-cooperative attempts were .26-.27), whereas indirect regulation attempts were not significantly associated with behavior change. Subsequent studies have found an association between direct regulation attempts and behavior change to the extent that relationship problems are important and changeable (Baker & McNulty, 2015;McNulty & Russell, 2010).…”
Section: Previous Research On Regulation Attempts To Resolve Interper...mentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that direct regulation attempts, regardless of opposing versus cooperative, were significantly associated with increased partner behavior change (standardized partial regression coefficients of direct-opposing attempts were .23, and standardized partial regression coefficients of direct-cooperative attempts were .26-.27), whereas indirect regulation attempts were not significantly associated with behavior change. Subsequent studies have found an association between direct regulation attempts and behavior change to the extent that relationship problems are important and changeable (Baker & McNulty, 2015;McNulty & Russell, 2010).…”
Section: Previous Research On Regulation Attempts To Resolve Interper...mentioning
confidence: 99%
“…A study of conflict in romantic couples showed that the less confident an actor was about resolving relationship problems, the less motivated the actor was to change their behavior (Baker & McNulty, 2015).…”
Section: Because Actors Perceived That Actions Were Difficult To Change?mentioning
confidence: 99%
“…(P5 J38, 132, 242-245) Nargis ( 2012) discovered that preschoolaged children experience a reduction in the amount of time they spend with their mothers when their mothers are engaged in employment, often resulting in a decrease of up to 2 hours per day. Baker & McNulty (2015) suggest that in order to maintain a happy marriage, it is essential to reestablish a strong connection with one's partner and prioritize the marriage, as it has a significant impact on all other aspects of life.…”
Section: Aspirations Based On the Experiences Of Working-student-mothersmentioning
confidence: 99%
“…Another limitation of the present research is that there were not enough studies to meta-analyze all theoretically and empirically important individual differences acknowledged within the partner regulation literature. For example, negative-direct partner regulation is shown to be particularly harmful for people with low self-esteem (Jayamaha & Overall, 2015) or those experiencing depression (Baker & McNulty, 2015). Further research and replication of findings is therefore warranted to provide clarity as to the conditions under which partner regulation may be associated with relationship quality and success.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%